Risk‐taking behavior in juvenile myoclonic epilepsy. Issue 12 (18th October 2013) - Wandschneider, Britta; Centeno, Maria; Vollmar, Christian; Stretton, Jason; O'Muircheartaigh, Jonathan; Thompson, Pamela J.; Kumari, Veena; Symms, Mark; Barker, Gareth J.; Duncan, John S.; Richardson, Mark P.; Koepp, Matthias J.
Summary Objective Patients with juvenile myoclonic epilepsy (JME) often present with risk‐taking behavior, suggestive of frontal lobe dysfunction. Recent studies confirm functional and microstructural changes within the frontal lobes in JME. This study aimed at characterizing decision‐making behavior in JME and its neuronal correlates using functional magnetic resonance imaging (fMRI). Methods We investigated impulsivity in 21 JME patients and 11 controls using the Iowa Gambling Task (IGT), which measures decision making under ambiguity. Performance on the IGT was correlated with activation patterns during an fMRI working memory task. Results Both patients and controls learned throughout the task. Post hoc analysis revealed a greater proportion of patients with seizures than seizure‐free patients having difficulties in advantageous decision making, but no difference in performance between seizure‐free patients and controls. Functional imaging of working memory networks showed that overall poor IGT performance was associated with an increased activation in the dorsolateral prefrontal cortex (DLPFC) in JME patients. Impaired learning during the task and ongoing seizures were associated with bilateral medial prefrontal cortex (PFC) and presupplementary motor area, right superior frontal gyrus, and left DLPFC activation. Significance Our study provides evidence that patients with JME and ongoing seizures learn significantly less from previous experience. Interictal dysfunction within "normal" working memory networks, specifically, within the DLPFC and medial PFC structures, may affect their ability to learn.